2003
DOI: 10.1002/pamm.200310322
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ship–Motion

Abstract: The ship capsizing problem is one of the major challenges in naval architecture. The Current stability criteriaCurrent stability criteria are based on static assumptions. The roll-restoring moments, called righting moments in calm water, are calculated at various heeling angles. By dividing the righting moment by the weight of the ship the righting lever curves, Figure 1, are obtained. The slope of the righting lever curve at 0• is called initial stability or metacentric height GM . National and internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The hydrostatic forces are calculated fully nonlinear, the calculation of the hydrodynamic forces bases on the strip theory for instationary flows. Two capsize scenarios have been found previously [4] and show the importance of a nonlinear analysis. With the applied method dangerous and non-dangerous regions of ship operations can be determined.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…The hydrostatic forces are calculated fully nonlinear, the calculation of the hydrodynamic forces bases on the strip theory for instationary flows. Two capsize scenarios have been found previously [4] and show the importance of a nonlinear analysis. With the applied method dangerous and non-dangerous regions of ship operations can be determined.…”
mentioning
confidence: 56%
“…When describing hydrodynamics, the history of the flow is very important for calculating the actual state of the flow [2], so a system of integro-differential-equations is needed for the further bifurcation analysis. Two kinds of capsize scenarios were detected [4] and it can be shown that increasing wave-height does not always lead to increasing roll amplitudes. This indicates the importance of the usage of full dynamical models in stability analysis of floating structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The electromagnetic subsystem is inducing current i, and L is inductance, R is electrical resistance, where Rc is coil resistance and Rd is load resistance, and R = Rc + Rd. The VEHD dynamics is described by system of ordinary differential equation (see [7][8][9][10][11], [14,15]) J```c +m 2 (-x/r) + b1(`-x`/r) = sin ( t) (1) mx``-m 2 (x/r) -b1(`-x`/r) + mi = 0 (2) Li`+ Ri -ex`-r`= 0 (3) where `=d/dt, m is the linkage factor between mechanical and electromagnetic subsystems in mechanical terms, e is the linkage factor between electromagnetic and mechanical subsystems in electromagnetic terms, and r is the distance from a centre of vessel mass to VEHD location.…”
Section: The Model Of Pitching Boat Equipped Byvehdmentioning
confidence: 99%
“…The marine vessels are experiencing different types of dynamic loads during operation [1,2]. One of the results of dynamic loads is the various kinds of vessel's oscillations.The authors selected one type of oscillations known as "pitching" for study in that paper.…”
Section: Introductionmentioning
confidence: 99%